RELATIONSHIP OF MATERNAL SELF EFFICACY, SOCIAL SUPPORT WITH POSTPARTUM DEPRESSION - Hartati, Dwi; Raden, Abkar; Kartini, Farida (Jurnal Kesehatan - STIKes Prima Nusantara, 2020)
Introduction: The high level of postpartum depression in postpartum mothers, which can affect the mother's skills in caring for and caring for her baby, requires self-efficacy and maternal social support for post-partum mothers so that the level of postpartum maternal depression can be reduced.Purpose: The purpose of this scoping review is to map available evidence  to the relationship maternal self efficacy, social support with depression postpartum.Methods: In this scoping review, the authors identify studies that explain the relationship between maternal self-efficacy, social support with postpartum depression from three databases (PubMed, Proquest, and Science Direct). Searches are limited to studies published in English and present data for the period 2009-2019. The identified research was reviewed using the PRISMA Flowchart. Studies with quantitative designs related to the relationship maternal self-efficacy, social support with postpartum depression are then selected for review.Results:  From a total of four articles that have been reviewed, two sub-themes are maternal relationship self-efficacy with postpartum depression and relationship social support with postpartum depression.Conclusion:  From this review, some pieces of evidence show that there is a significant relationship between maternal self-efficacy, social support with postpartum depression. All studies included in the review have limitations related to the research design or sample collection procedures